2021
DOI: 10.1007/s12649-021-01448-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Paper vs. Bioplastic Bags on Food Waste Collection and Processing

Abstract: Purpose The most abundant among the separately collected waste materials in Italy is food waste. This research aims to evaluate the influence of the type of collection bag on the food waste management chain. In Italy, the food waste collection is mainly based on bioplastic bags. As an alternative, a new type of recycled paper bag shows potential advantages. Methods The two types of collection bag were compared evaluating the weight loss of food waste durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…During the household storage, the waste inserted into each bag (2 kg) undergoes a weight loss because of the evaporation of a certain amount of its moisture. According to the experimental tests described in Dolci et al (2021), the following average losses were observed and considered in this assessment: 10.2% for the dedicated bioplastic bags, 8.7% for the bioplastic shopper bags and 12.9% for the paper bags. This aspect leads to different amounts of food waste that are subsequently collected.…”
Section: Impact Categories and Characterisation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…During the household storage, the waste inserted into each bag (2 kg) undergoes a weight loss because of the evaporation of a certain amount of its moisture. According to the experimental tests described in Dolci et al (2021), the following average losses were observed and considered in this assessment: 10.2% for the dedicated bioplastic bags, 8.7% for the bioplastic shopper bags and 12.9% for the paper bags. This aspect leads to different amounts of food waste that are subsequently collected.…”
Section: Impact Categories and Characterisation Methodsmentioning
confidence: 99%
“…a lower amount of waste to be collected). This aspect can be favoured by the adoption of proper collection bags that can favour the partial evaporation of water (Dolci et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, plastic waste generated from single use plastic bags has prompted much debate, forcing many governments and municipalities to adopt or promote alternatives and restrictions to their usage. Replacing petroleumbased disposable carrier bags with compostable ones has become a common option in some countries, along with use of reusable totes and paper bags and other solutions (Battista et al, 2021;Dolci et al, 2021). For example, lightweight plastic bags (thickness < 50 µm) were initially banned in Italy in 2011, and in 2018 the ban was extended to ultra-thin (UT) plastic bags (thin < 15 µm).…”
Section: Introductionmentioning
confidence: 99%